The reemergence of pertussis in immunized populations: a case study. - Domínguez D (Clinical Laboratory Science)
OBJECTIVE: To present a case of classical pertussis occurring in previously vaccinated male siblings, 11 and 13 years of age, living in El Paso TX; also to present an overview and update of the changing epidemiology of pertussis including pathophysiology, diagnosis, and treatment. DESIGN: Nasopharyngeal swabs and blood samples were collected from two male siblings, 11 and 13 years of age, presenting with cold-like symptoms and persistent cough during the second week of infection. Nasopharyngeal swabs were plated onto Bordet-Gengou agar plates and incubated for 48 hours. Blood samples were analyzed for the presence of antibodies (IgM and IgA) against Bordetella pertussis antigens using indirect enzyme linked immunosorbent assay (ELISA). SETTING: Cultures and serological analysis was conducted at the University of Texas at El Paso, Clinical Laboratory Science Program Research facility. RESULTS: Bacterial cultures of both children were positive for Bordetella pertussis and the sera revealed positive IgM and IgA antibodies (> 11 PANBIO UNITS) against a mixture of antigens including: pertussis toxin, filamentous hemagglutinin, pertactin, and fimbriae. CONCLUSIONS: Pertussis immunity wanes overtime, leaving most adolescents and adults susceptible to infection. Physicians must be prepared to diagnose and treat pertussis in any age group regardless of vaccination status.